Traveling Wave Solutions in a Reaction-Diffusion Epidemic Model - Sheng Wang; Wenbin Liu; Zhengguang Guo; Weiming Wang (Abstract and Applied Analysis)
We investigate the traveling wave solutions in a reaction-diffusion epidemic model. The existence of the wave solutions is derived through monotone iteration of a pair of classical upper and lower solutions. The traveling wave solutions are shown to be unique and strictly monotonic. Furthermore, we determine the critical minimal wave speed.